Спеціально-кримінологічні заходи протидії злочинам проти державного суверенітету і територіальної цілісності України - Носач, А. В.; Nosach, A. V. (Право.ua. - 2020. - № 1. - С. 97-101, 2020)
Визначено основні спеціальні заходи протидії злочинам проти державного суверенітету і територіальної цілісності України як одного з напрямків правоохоронної діяльності. Окреслено основні напрями запобіжної роботи на етапі виявлення, усунення й нейтралізації причин та умов негативних явищ, які виникли чи можуть виникнути й детермінувати злочини проти державного суверенітету і територіальної цілісності. Акцентовано увагу, що для ефективного застосування спеціальних заходів протидії цим злочинам особливого значення набуває чітка регламентація правового статусу суб’єктів правоохоронної діяльності, розмежування їх повноважень, удосконалення форм та методів діяльності.

The publication is focused on determining the main special measures to counteract crimes against state sovereignty and territorial integrity of Ukraine as one of the areas of law enforcement activity. The author has outlined the basic areas of preventive work at the stage of identifi cation, elimination and neutralization of the causes and conditions of negative phenomena that have arisen or can occur and determine crimes against state sovereignty and territorial integrity. Particular attention has been paid to the fact that the clear regulation of the legal status of law enforcement subjects, the allocation of their powers, the improvement of forms and methods of their activity are of particular importance for effective implementation of special measures to counteract these crimes. It has been emphasized that there is an urgent need to differentiate the criminological impact of special measures to counteract terrorism as one of the most dangerous crimes encroaching on the national security and territorial integrity, depending on the stages of the organization and implementation of the prevention process. The author has summarized that the system of measures of special counteraction to crimes that encroach on the territorial integrity and state sovereignty of Ukraine should be conceptually considered in two senses, fi rst of all, as the essence and content of the mechanism of combating crime of a certain kind based on established and scientifi cally proven data concerning its tendencies, characteristics, regularities and manifestations as a phenomenon of modern society; secondly, as a defi ning strategic vector, a basic way to deploy and execution of a practical implementation of counteraction to crimes that encroach on state sovereignty and territorial integrity of Ukraine.

Определены основные специальные меры по противодействию преступлениям против государственного суверенитета и территориальной целостности Украины как одного из направлений правоохранительной деятельности. Акцентировано внимание, что для эффективного применения специальных мер противодействия этим преступлениям особое значение приобретает четкая регламентация правового статуса субъектов правоохранительной деятельности, разграничение их полномочий, усовершенствование форм и методов деятельности.
Keywords: протидія злочинності; crime prevention; противодействие преступности; спеціально-кримінологічні заходи; special criminological measures; специально-криминологические мероприятия; державний суверенітет; state sovereignty; государственный суверенитет; територіальна цілісність; territorial integrity; территориальная целостность